Eclipsing Stellar Flare on the Demon Star Algol Binary System Observed during the MAXI-NICER Follow-up Campaign in 2018 - Nakayama, Kazuya; Iwakiri, Wataru Buz; Enoto, Teruaki; Inoue, Shun; Notsu, Yuta; Gendreau, Keith; Arzoumanian, Zaven; Hamaguchi, Kenji; Mihara, Tatehiro (My University, 2025)
Algol is a well-known eclipsing binary hosting an active and variable star that exhibits frequent stellar flares. Here, we report our pre-planned and coordinated rapid X-ray follow-up observations of an eclipsing flare on Algol. The Monitor of All-sky X-ray Image (MAXI) detected a flare on Algol at 05:52 UT on 2018 July 4. Subsequently, we carried out a prompt X-ray monitoring with the Neutron star Interior Composition Explorer (NICER) starting at 19:45 UT on the same day, and the observation ended at 06:02 UT on 2018 July 6. During the decaying phase of the flare, we successfully detected a 5.8-hour-long eclipse, corresponding to the secondary eclipse in which Algol A blocks the line of sight to Algol B. During the eclipse, the 2–10 keV X-ray flux is decreased to 20% level from 1.9 × 10⁻¹⁰ erg cm⁻² s⁻¹ to 4.5 × 10⁻¹¹ erg cm⁻² s⁻¹ . We found a configuration of the flare size and location to explain the X-ray observations; e.g., the flare occurred at the latitude 45°S of the Algol B surface with a flare height of 1.9 × 10¹¹ cm, corresponding to 0.8 times the stellar radius of Algol B, giving 80% obscuration of the flare loop by Algol A. The apparent absorption increase before the eclipse might originate from coronal mass ejection (CME) in the line of sight ejected during the flare.
Keywords: Astrophysics - High Energy Astrophysical Phenomena; Astrophysics - Solar and Stellar Astrophysics